TRENDS AND DEVELOPMENT OF ISLAMIC DA’WAH RESEARCH IN DIGITAL MEDIA: A BIBLIOMETRIC ANALYSIS (2016–2023) - Moh Ali; Burhan Burhan (Karimiyah: Journal of Islamic Literature and Muslim Society, 2025)
The rapid digitalization of communication channels has fundamentally reshaped the landscape of Islamic da’wah, transforming how Islamic teachings are disseminated, received, and negotiated in the contemporary world. This study presents a comprehensive bibliometric analysis of scholarly literature on Islamic da’wah research in digital media published between 2016 and 2023. Drawing on 152 peer-reviewed articles retrieved from Scopus, Web of Science, and Google Scholar databases, this study employs VOSviewer and Bibliometrix R-package to map intellectual structures, publication trends, keyword co-occurrences, and collaborative networks within this emerging field. Findings reveal a remarkable 1,075% increase in annual publication output over the study period, with accelerated growth particularly evident from 2020 onward—coinciding with global pandemic-induced digital migration. Six principal thematic clusters were identified: (1) platform-specific da’wah practices (YouTube, Instagram, TikTok); (2) digital religious authority and identity construction; (3) da’wah communication strategies; (4) Islamic education and digital literacy; (5) ethics, religious moderation, and social inclusion; and (6) bibliometric and scientometric meta-analyses of the da’wah field. Indonesia emerges as the dominant contributor, accounting for 61.2% of all publications, followed by Malaysia and Saudi Arabia. The analysis further identifies critical research gaps, including underexplored topics such as artificial intelligence-mediated da’wah, algorithmic influence on Islamic narrative formation, and cross-cultural reception studies. This study offers a robust intellectual map of the field and provides evidence-based direction for future scholars, policymakers, and Islamic communication practitioners.